Preparation and Evaluation of Beta sitosterol Nanogel: A Carrier Design for Targeted Drug Delivery system - Inamdar, Yashashri Mohan; Rane, Bhushan; Jain, Ashish (Asian Journal of Pharmaceutical Research and Development, 2018)
Transdermal drug delivery system is promising but challenging system available for local as well as systemic effect of the drug. The prolonged residence of drug formulation in the skin is important for transdermal drug delivery. Nanogel drug delivery has remained as one of the most challenging task. The objective of the investigation was to develop a nanogel with reduced particle size in order to improve the bioavailability of the hydrophobic drug. The objective of the controlled and sustained delivery is to provide and maintained adequate concentration of drugs at the site of action. Nanogels based materials have high drug loading capacity, biocompatibility and biodegradability which are key points to design the drug delivery system effectively. Drug molecules loaded into the nanogel need to be retained and not to be transported out or leak prematurely while circulating in order to provide maximum therapeutic effects and minimum toxicity or side effects. The present study is to formulate nanosizes dispersion of Beta sitosterol by nanoprecipitation method and incorporating it into the gelling agent to produce nanogel by dispersion method. 1% of carbopol 934 shows better in-vitro drug release than the other concentrations of carbopol 934.